2016
DOI: 10.3389/fcimb.2015.00097
|View full text |Cite
|
Sign up to set email alerts
|

Total Antioxidant Capacity and Total Oxidant Status in Saliva of Periodontitis Patients in Relation to Bacterial Load

Abstract: The detection of salivary biomarkers has a potential application in early diagnosis and monitoring of periodontal inflammation. However, searching sensitive salivary biomarkers for periodontitis is still ongoing. Oxidative stress is supposed to play an important role in periodontitis progression and tissue destruction. In this cross-sectional study, we investigated total antioxidant capacity (TAC) and total oxidant status (TOS) in saliva of periodontitis patients compared to healthy controls and their relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 57 publications
1
48
2
1
Order By: Relevance
“…Severe tissue destruction associated with AP may be due to the reduced total antioxidant capacity of these patients. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The present study was carried out for the assessment of one enzymatic antioxidant, SOD, another nonenzymatic antioxidant uric acid, TAS, and lipid peroxidation status in serum and GCF of CP and AP patients compared with healthy controls. The objective of the assessment was for observing the possible differences in local and systemic antioxidant status between CP and AP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe tissue destruction associated with AP may be due to the reduced total antioxidant capacity of these patients. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The present study was carried out for the assessment of one enzymatic antioxidant, SOD, another nonenzymatic antioxidant uric acid, TAS, and lipid peroxidation status in serum and GCF of CP and AP patients compared with healthy controls. The objective of the assessment was for observing the possible differences in local and systemic antioxidant status between CP and AP.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the salivary TOS between periodontitis patients and healthy controls was not significant. 13 Severe tissue destruction associated with aggressive form of periodontitis may be due to the reduced total antioxidant capacity of the patients. 14 Action of antioxidant enzyme SOD triggered against superoxide, ROS, in inflammatory pathways is for protection against connective tissue breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,13 Measuring the total antioxidant capacity of the saliva is a routine method in various studies. 6,9,15,[17][18][19][20][21][22][23] In a research by Chapple et al, 18 superoxide dismutase (SOD) decreased in deep periodontal pockets, but following the first phase of periodontal therapy, the level of total antioxidants in the gingival crevicular fluid (GCF) increased. Similar to this study, Diab-Ladki et al, 9 Sculley et al 15 and Brock et al 19 reported that the total antioxidant capacity of the saliva of periodontally compromised patients decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Total antioxidant capacity has been used previously as a salivary biomarker related to periodontal disease and dental caries. Decreases in total antioxidant capacity have been linked to periodontal disease 89 .…”
Section: Discussionmentioning
confidence: 99%